Understanding the use intention and influencing factors of telerehabilitation in people with rehabilitation needs: a cross-sectional survey - Wang, Mao-Yuan; Chen, Hong; Gong, Cheng; Peng, Xu-Miao; Zhong, Yan-Biao; Wu, Chun-Mei; Luo, Yun; Wu, Yong-Qiang (Frontiers in Public Health, 2023)
Objective: This study aims to investigate the use intention and influencing Factors of telerehabilitation in people with rehabilitation needs.: This cross-sectional survey recruited a total of 183 participants with rehabilitation needs from May 2022 to December 2022. Sociodemographic and medical data were collected by a structured questionnaire. The factors influencing the use intention of telerehabilitation were measured by the extended UTAUT model. Multiple hierarchical regression analyses were performed. Results: A total of 150 valid questionnaires were included for analysis. The results indicated that the use intention of telerehabilitation was overall high in people with rehabilitation needs. Health condition (β = -0.21, P = 0.03), performance expectancy (β = 0.21, P=0.01), facilitating conditions (β = 0.25, P=0.03), perceived trust (β = 0.25, P<0.01), and self-efficacy (β = 0.19, P=0.04) were significant factors influencing the use intention of telerehabilitation. Conclusions: Overall use intention of telerehabilitation is high in individuals with rehabilitation needs. Health conditions, performance expectancy, facilitating conditions, perceived trust, and self-efficacy are important factors influencing the use intention of telerehabilitation in individuals with rehabilitation needs.